2011
DOI: 10.1021/la201548k
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Superhydrophobicity and Low Velocity Impact Icephobicity of Acetone-Functionalized Carbon Nanotube Films

Abstract: We present a simple method to produce carbon nanotube-based films with exceptional superhydrophobicity and impact icephobicity by depositing acetone-treated single-walled carbon nanotubes on glass substrates. This method is scalable and can be adopted for any substrate, both flexible and rigid. These films have indicated a high contact angle, in the vicinity of 170°, proved both by static and dynamic analysis processes. The dynamic evaporation studies indicated that a droplet deposited on the treated films eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 54 publications
1
78
0
Order By: Relevance
“…Significantly delayed ice formation [3,10,12,13,15,16,23,26] and reduced ice adhesion or accumulation [3,10,[15][16][17]19,21,25] have been reported for various SHSs. Theoretical models have also been developed, demonstrating how SHSs can delay ice formation from impinging water droplets [9,11,13], which is in good agreement with experimental work [3,14,25,26].…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…Significantly delayed ice formation [3,10,12,13,15,16,23,26] and reduced ice adhesion or accumulation [3,10,[15][16][17]19,21,25] have been reported for various SHSs. Theoretical models have also been developed, demonstrating how SHSs can delay ice formation from impinging water droplets [9,11,13], which is in good agreement with experimental work [3,14,25,26].…”
mentioning
confidence: 95%
“…The design and use of surfaces/coatings with minimum ice adherence and reduced ice accumulation is still actively considered as the most appealing and universal approach to the problem [3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Most of the existing studies on anti-ice surfaces are focused on the reduction of ice adhesion strength [1,[5][6][7][8]10,[19][20][21][22][23][24] or delayed ice nucleation/formation [3,9,12,13,23,25,26]. Therefore lately the research in this area has been chiefly focused on the use and development of superhydrophobic surfaces (SHSs) for preventing ice formation and accumulation [4,[9][10][11][13][14][15][16][17][18][19]…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have further shown the good correlation between superhydrophobicity and icephobicity [52,[150][151][152], although a few studies did not agree with this aspect and showed the inverse results [55,56]. In order to compare and come to conclusion regarding the relationship between hydrophobicity and icephobicity, several factors should be considered such as: the method of ice accumulating on a surface, type of the accumulated ice, and the morphology of the surface.…”
Section: V-3-icephobicitymentioning
confidence: 99%